Nondiscriminating Foreclosure and Voluntary Liquidating Costs - Wang, Ko; Young, Leslie; Zhou, Yuqing (Review of Financial Studies, 2002)
Since liquidation and bankruptcy are costly, researchers have tried to find out why the claimants of a troubled firm do not work out a deal to avoid these costs. In this article we show that if a creditor has to deal with multiple borrowers who might default, it may be optimal for the creditor to randomly reject requests for a loan workout. We further demonstrate that the optimal acceptance rate used by a creditor is positively related to the liquidating cost and negatively related to the default benefit. Our model is particularly relevant when analyzing the default decisions of mortgage borrowers and small business owners.